Inclusion of Azolla pinnata as an unconventional feed of Zaraibi dairy goats, and effects on milk production and offspring performance - Hassanein, Hanan A. M.; Maggiolino, Aristide; Abou El-Fadel, Magdy H.; De Palo, Pasquale; El-Sanafawy, Heba A.; Hussein, Ahmed M.; Salem, Abdelfattah Z. M. (Frontiers in Veterinary Science, 2023)
Introduction This study investigated the effects of using sun-dried Azolla (Azolla pinnata) meal (SDAM) protein to replace sunflower meal protein in the diets of Zaraibi goats dams on nutrient digestibility, milk yield, composition, and economics. Method A total of 15 Zaraibi goats (32.23 ± 0.2 kg) were randomly divided into three equal groups, R1, R2, and R3 which were fed based on average milk production. The basal ration was a concentrated feed mixture containing 0, 10, and 20% SDAM which replaced 0, 25, and 50% of sunflower meal protein in the respective groups. Results Nutrient digestibility and feeding values were improved with R3 goats, which had the highest level of azolla (20%) R3 versus R2 and R1 goats. The total volatile fatty acid (TVFA) concentration in the in-rumen liquor was elevated by increasing the level of azolla up to 20% in R3 goats. The results revealed significantly higher (P<0.05) mean milk yield in the SDAM groups in comparison to R1 (1184, 1131 and 1034 respectively). The beneficial effects of the tested groups were observed in milk composition, milk fat, milk protein, and non- fats solids. Whereas the milk fat yield was higher in the SDAM group in comparison with the control group (40.84, 37.20, and 33.92). Ration inclusion of SDAM improved economic feed efficiency (relative feed cost and relative daily profit) and had a significant effect on the yield of milk constituents. In general, using up to a level of 20% SDAM in place of sunflower meal for feeding lactating Zaraibi goats improved milk production, milk fat yield, and cost-benefit ratio. Discussion This study recommended that, inclusion of sun-dried azolla meal up to 20%, as an unconventional feed for Zaraibi dairy goats and offspring, improved milk production and economically feed efficiency.